Mechanism of action and relationship between structure and biological activity of ctx-ha: A new ceratotoxin-like peptide from hypsiboas albopunctatus - Cespedes, Graziely Ferreira [UNESP]; Lorenzón, Esteban Nicol [UNESP]; Vicente, Eduardo Festo [UNESP]; José, Maria [UNESP]; Giannini, Soares Men [UNESP]; Fontes, Wagner; Castro, Mariana De Souza; Cilli, Eduardo Maff [UNESP] (Bentham Science Publishers, 2012)
The increase in bacterial resistance to current antibiotics has led to the development of new active molecules. We have isolated the antimicrobial peptide Ctx-Ha from the skin secretion of the frog Hypsiboas albopunctatus. The aim of the present work was to elucidate the mechanism of action of this new antimicrobial peptide. The sequence similarity with Ceratotoxin, the pore size, and the pore-like release of carboxyfluorescein from vesicles indicated that Ctx(Ile21)-Ha has a mechanism of action based on the barrel- stave model. In a second part of this work, we synthesized three analogues to provide information about the relationship between the peptide's structure and its biological activity. Ctx(Ile21)-Ha-VD 16, Ctx(Ile21)- Ha-VD 5,16 and Ctx(Ile21)-Ha-I9K were designed to disrupt the peptide's helical structure and change the hydrophobicity/ hydrophilicity and amphipathicity of the apolar face in order to uncouple the antimicrobial activity of Ctx(Ile21)-Ha from its hemolytic activity. To evaluate the effects of the amino acid substitutions on peptide conformation, secondary structure was accessed using CD measurements. The peptides presented a high amount of α-helical structure in the presence of TFE and LPC. The CD data showed that destruction of the amphipathic α-helix by the replacing isoleucine by lysine is less harmful to the structure than D-amino acid substitutions. Biological tests demonstrated that all peptides have activity. Nevertheless, the peptide Ctx(Ile21)-Ha-I9K showed the highest value of therapeutic index. Our findings suggest that these peptides are potential templates for the development of new antimicrobial drugs. These studies highlight the importance of single amino acid modification as a tool to modulate the biological activity of antimicrobial peptides. © 2012 Bentham Science Publishers.
Keywords: Antimicrobial peptides; Barrel-stave mechanism; Ceratotoxin; Circular dichroism; D-amino acids; Structure-activity relationship.